The Moral Argument For The Non-Existence Of God - Krettek, Thomas (Philosophy & theology, 1997)
I highlight a dimension of the debate about the problem of evil and the existence of God that has loomed on the periphery and consider how, if at all, a specific consideration of that dimension can move the debate forward. My contention is that there is specific version of moral argument for the non-existence of God that is implicit in the problem of evil. This argument is a strategic but suppressed premise that strengthens or undermines the persuasiveness of arguments for or against the existence of God. This argument needs to be thematized if the debate between theism and atheism is to move forward.